Studi Literatur : Potensi Ekstrak Bioaktif dari Daun Kemangi (Ocimum basillicum) sebagai Gel Anti-Acne - Kamilia Zukhrufillah, Dinda; Rosdiana, Laily; Roqobih, Fikky Dian (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
Acne is a common skin problem, particularly during adolescence. It can affect both appearance and skin health. Literature studies suggest that basil leaf extract has potential as an active ingredient in anti-acne gel due to its antibacterial and anti-inflammatory properties. This article aims to identify the antibacterial potential and activity of basil leaf extract against Staphylococcus epidermidis bacteria and to develop an anti-acne gel using this natural ingredient. The research method employed is a qualitative, non-experimental study using a systematic review approach. The literature review results indicate that basil leaf extract is promising as an active ingredient for anti-acne gel due to its antibacterial and anti-inflammatory properties. Active compounds in basil leaves, such as essential oils, flavonoids, and tannins, have been proven to reduce inflammation, inhibit the growth of acne-causing bacteria, and improve overall skin condition. However, attention must be given to the extract's concentration and the potential for irritation on sensitive skin. In conclusion, gel containing basil leaf extract holds potential as a natural solution for acne treatment. Nevertheless, its use should be carefully considered for individuals with sensitive skin.